Scrub typhus: emerging as a co-infection of acute undifferentiated febrile illness in children in a district hospital of Eastern India - Bandyopadhyay, Santanu; Amin, S. Ruhul (International Journal of Contemporary Pediatrics, 2023)
Scrub typhus, a zoonosis, caused by Orientia tsuttsutgamushi is transmitted to man through bite of infected tromboculid mite. It is endemic in India as other other South-east Asia countries of Tsuttsutgamuhi triangle and affects children as well. It generally presents as an acute febrile illness with non-specific features like headache rash, lymphadenopathy resembling many other commonly prevalent febrile infections. An eschar, though pathognomonic of Scrub typhus, is often missed clinically. Therefore, a high index of clinical suspicion is essential to establish a diagnosis of Scrub typhus and hence it remains usually under-diagnosed in any undifferentiated febrile illness. In this case series including three cases, we decided to rule out Scrub typhus as a co-infection when there was persistence of fever associated with thrombocytopenia even after ongoing treatment of the primarily diagnosed infection. An eschar was incidentally detected in one case only.